2022
DOI: 10.1158/1055-9965.epi-21-1252
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Levels of Copper and Zinc and Breast Cancer Risk in the ORDET Cohort

Abstract: Background: Case-control studies show that copper (Cu) is high and zinc (Zn) low in blood and urine of breast cancer (BC) women compared to controls. Methods: To assess whether pre-diagnostic Cu and Zn are associated with BC risk, odds ratios (OR) of BC according to Cu, Zn, and Cu/Zn ratio in plasma and urine were estimated in a nested case-control study within the ORDET cohort, using conditional logistic regression adjusted for multiple variables: First 496 BC cases and matched controls, diagnosed {greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous epidemiological studies on cancer survival have linked high serum copper levels and copper/zinc ratio with lower cancer survival but have shown inconclusive results regarding zinc levels and cancer survival [ [2] , [3] , [4] , [5] ]. Specific to breast cancer, there are a few studies on copper, zinc and copper/zinc levels in relation to breast cancer risk [ 1 , 25 , 26 ]. To our knowledge, no previous study has investigated the association between copper and copper/zinc and breast cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies on cancer survival have linked high serum copper levels and copper/zinc ratio with lower cancer survival but have shown inconclusive results regarding zinc levels and cancer survival [ [2] , [3] , [4] , [5] ]. Specific to breast cancer, there are a few studies on copper, zinc and copper/zinc levels in relation to breast cancer risk [ 1 , 25 , 26 ]. To our knowledge, no previous study has investigated the association between copper and copper/zinc and breast cancer survival.…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal expression of SOD1 is linked to several cancers [ 65 , 66 ]. Pala et al conducted a prospective study and observed that elevated blood Cu/Zn levels could serve as an early marker and a crucial risk factor for breast cancer development [ 67 ]. According to a meta-analysis study, the serum Cu levels in patients with breast cancer were considerably higher than those in healthy controls and women with benign breast disease.…”
Section: Copper/zinc Ratio and Breast Cancermentioning
confidence: 99%
“…Unsurprisingly, given the crucial nature of zinc in many enzymatic reactions and physiological processes, low zinc levels are associated with a variety of disease states. Low levels of zinc have been reported in a range of cancers, with increasing evidence suggesting that low zinc levels in serum, plasma, and tissues may be linked to carcinogenesis [ 17 , 18 ]. In this review, we will present the recent evidence that low zinc levels in a variety of situations are a hallmark of various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of these meta-analyses, additional clinical studies have shed further light on the close association between low zinc levels in tissues and serum and breast cancer. For example, in their 2022 study, Pala et al [ 17 ] assessed the association between pre-diagnostic copper and zinc levels in the plasma and urine of women later diagnosed with breast cancer. The authors found that patients with a plasma copper/zinc ratio or a plasma and urine copper/zinc ratio in the upper tertile of the patient cohort had a significantly higher risk of developing breast cancer than those in the lower tertiles.…”
Section: Introductionmentioning
confidence: 99%